Vicious Circle or New Paradigm? Exploring the Impact of Shadow Economy on Labour Market in Latin America and Eurozone - Sangeeta Khorana; Santiago Caram; Marco Biagetti (Global Labor Organization (GLO), 2021)
The relationship between shadow economy (or informal economy) and development has been extensively researched. But there is a lack of consensus on how institutional quality affects the size of informal economy in any country. Using the Kuznets Curve hypothesis we assess the relationship between institutional quality and the size of SE for a group of Latin American and Eurozone countries for 1991-2015. We examine the rationale of the 'exclusion' and 'escape' theories in short and long-run with the multiple indicators multiple causes (MIMIC) model. We use two techniques, namely an instrumental variable (IV) and Fully Modified OLS (FMOLS) approach. The results show positive and a significant relationship between labour productivity and the size of the shadow economy. We also find that the size of the informal sector is related to the institutional framework, and while the size of the informal sector varies across countries, both formal and informal sectors can co-exist in the long run. High corruption together with an excessive tax burden and adverse socio-economic conditions impact the size of the informal sector in an economy.
Keywords: O17; O40; O43; C23; C26; 330; Shadow Economy; informal sector; development; cointegration; causality